1995
DOI: 10.1074/jbc.270.40.23540
|View full text |Cite
|
Sign up to set email alerts
|

L-Tryptophan 2′,3′-Oxidase from Chromobacterium violaceum

Abstract: L-Tryptophan 2,3-oxidase, an amino acid ␣,␤-dehydrogenase isolated from Chromobacterium violaceum, catalyzes the formation of a double bond between the C ␣ and C ␤ carbons of various tryptophan derivatives provided that they possess: (i) a L-enantiomeric configuration, (ii) an ␣-carbonyl group, and (iii) an unsubstituted and unmodified indole nucleus. Kinetic parameters were evaluated for a series of tryptophan analogues, providing information on the contribution of each chemical group to substrate binding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Its structure is related to tryptophan and serotonin but the enzymatic production of α,β-dehydrotryptophan in humans has not yet been reported. However, the presence of Ltryptophan 2',3'-oxidase and related enzymes -capable of production of α,β-dehydrotryptophan (indole-3-acrylic acid) -has been described in some common bacteria which may populate the gut (see Roberts and Rosenfeld 1977, Zavala et al 1983, Genet et al 1995. Hence, the exogenous (gut flora) source of IAG cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure is related to tryptophan and serotonin but the enzymatic production of α,β-dehydrotryptophan in humans has not yet been reported. However, the presence of Ltryptophan 2',3'-oxidase and related enzymes -capable of production of α,β-dehydrotryptophan (indole-3-acrylic acid) -has been described in some common bacteria which may populate the gut (see Roberts and Rosenfeld 1977, Zavala et al 1983, Genet et al 1995. Hence, the exogenous (gut flora) source of IAG cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this activity has been reported for the commensal microbiota of mackerel [128]. On the other hand, a tryptophan oxidase activity has been described as playing a role in the synthesis of the pigment violacein in the free living marine bacterium Chromobacterium violaceum [129]. Other violacein pigmented marine bacteria, such as Pseudoalteromonas luteoviolacea , have shown broad range l -amino acid oxidase activity [130].…”
Section: L-amino Acid Oxidasesmentioning
confidence: 99%
“…LAAO may act as defence or attack weapons via H 2 O 2 [11] or as ideal molecular mechanisms for the acquisition of nitrogen from diverse amino acid sources [12]. In addition, researches have showed that LAAO affects the relation of tumor cells with the immune system [13] and is involved in violacein synthesis [14]. So far, LAAO was found to be applied as catalysts in bio-transformation [15] and as part of biosensors in determination of the different forms (D-or L-) of free amino acids [16].…”
Section: Nhmentioning
confidence: 99%